2021
DOI: 10.1108/mip-10-2020-0457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humor climate within online brand community

Abstract: PurposeThis study examines the effects of the online brand community's (OBC) humor climate on the value cocreation (VCC) behavior of consumers using the affective events theory. It also evaluates the serial mediating roles of positive emotions and brand engagement and the moderating effect of membership duration.Design/methodology/approachThe authors collected data from 601 Chinese consumers of OBCs using an online questionnaire survey and applied structural equation modeling to analyze the data.FindingsThe au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…(2) There is a huge body of literature on online community climate and user’s value co-creation behavior [ 6 , 27 ], but the mechanism whereby the two interact with each other remains unclear. It is found that achievement need motivation plays a suppressing effect between controlling climate and user participation behavior, and power need motivation plays a suppressing effect between supporting climate and user citizenship behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) There is a huge body of literature on online community climate and user’s value co-creation behavior [ 6 , 27 ], but the mechanism whereby the two interact with each other remains unclear. It is found that achievement need motivation plays a suppressing effect between controlling climate and user participation behavior, and power need motivation plays a suppressing effect between supporting climate and user citizenship behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Since online communities, as an informal organization, are loose and open, community managers seldom intervene directly with users, but subtly influence their perceptions and behaviors by creating different community climates. Existing scholarship categorizes online community climate into humorous climate [ 27 ], social climate [ 28 ], team error management climate [ 29 ], virtual Brand Community’s Innovation climate [ 30 ] etc. Some scholars believe that multiple climates co-exist in the same community, which are related to each other and work together, such as an innovative climate and a social climate [ 8 ], a supportive, fair and ethical climate [ 6 ], and an innovative, interactive and controlling climate [ 26 ], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have established and examined several organizational climate concepts related to a particular aspect of the organizational environment, such as humor climate (Yang et al , 2021), service climate (Hoang, 2022) and supportive climate (Luthans et al , 2008). The authors focus on supportive climate, which social support theory (Shumaker and Brownell, 1984) defines as a multidimensional construct with different components in different contexts (Zhu et al , 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%